THE EFFECT OF THINK PAIR SHARE (TPS) LEARNING MODEL ON LEARNING THEME OF INDAHNYA KEBERSAMAAN SUBTEMA 2 TOGETHER IN DIVERSITY LEARNING LESSONS 1 CLASS IV STUDENTS IN 54 STATE ELEMENTARY SCHOOLS 54 LUBUKLINGGAU - lestari; Rudi Erwandi; Tio Gusti Satria (Yayasan Citra Dharma Cindekia, 2021)
This study aims to determine the effect of Think Pair Share (TPS) learning model on the Learning of the Beautiful Theme of Subtema 2 Together in Diversity Learning Lessons 1 Grade IV Students at SD Negeri 54 Lubuklinggau. The research method used is a pure experiment that there are two classes one class as an experimental class and the other class as a control class. Data collection techniques in this study used a test which provided as many as 20 test instruments and tested them so that they got valid questions that would be used as tests for students in the control class or in the experimental class. Data analysis techniques with steps, namely: after getting the scores of students in the control class and the experimental class then the next step to look for, on average, standard deviations, conduct normality test, homogeneity test and average test of two groups. The results showed that there was a significant influence on Think Pair Share (TPS) learning model on the Learning of the Beautiful Theme of Subtema 2 Together in Diversity Learning Lessons 1 Students in Class IV of SD Negeri 54 Lubuklinggau.